2022
DOI: 10.1016/j.eimc.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the immune response modification by lysophosphatidylcholine in the efficacy of antibiotic therapy of experimental models of peritoneal sepsis and pneumonia by Pseudomonas aeruginosa: LPC therapeutic effect in combined therapy

Abstract: Immune response stimulation may be an adjuvant to antimicrobial treatment. Here, we evaluated the impact of immune response modification by lysophosphatidylcholine (LPC) combined with imipenem or ceftazidime in murine models of peritoneal sepsis (PS) and pneumonia by Pseudomonas aeruginosa. Imipenem and ceftazidime-susceptible strain (Pa39), and imipenem and ceftazidime-resistant strain (Pa238) were used. Ceftazidime pharmacokinetic and pharmacodynamic parameters were determined. Therapeutic efficacy, and TNF-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Parra-Millan et al reported that LPC could trigger innate and specific humoral-mediated immunity as LPC administration regulated the immune response in the prognosis of ceftazidime-resistant Pseudomonas -induced infections ( 6 ). Moreover, in monocyte-derived dendritic cells, LPC could upregulate the CD86, HLA-DR , and CD40 genes expression ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parra-Millan et al reported that LPC could trigger innate and specific humoral-mediated immunity as LPC administration regulated the immune response in the prognosis of ceftazidime-resistant Pseudomonas -induced infections ( 6 ). Moreover, in monocyte-derived dendritic cells, LPC could upregulate the CD86, HLA-DR , and CD40 genes expression ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parra-Millan et al reported that LPC could trigger innate and specific humoral-mediated immunity as LPC administration regulated the immune response in the prognosis of ceftazidime-resistant Pseudomonas -induced infections ( 6 ). Moreover, in monocyte-derived dendritic cells, LPC could upregulate the CD86, HLA-DR , and CD40 genes expression ( 6 ). LPC increased the relative weights of bursa and thymus, and improved antibody production titers against Newcastle disease virus and sheep red blood cells in broilers ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to immunomodulation, different to immunoglobulins, have also been reported. In murine experimental models infected with ceftazidime-resistant P. aeruginosa , a combination of lysophosphatidylcholine—a modulator of the immune system—with ceftazidime and/or imipenem led to a greater decrease in the bacterial concentration in tissues compared with when these antibiotics were used as monotherapies ( Parra-Millán et al, 2020 ). Modulation of the immune system might circumvent antibacterial resistance, leading to an efficacious treatment of these infections ( Chiang et al, 2018 ), does not disrupt microbiota ( Schubert et al, 2015 ), and protects against reinfection ( Quintin et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, LPC preemptive treatment in combination with colistin, tigecycline or imipenem has improved the in vivo antibacterial activity of these antimicrobials in murine experimental peritoneal sepsis and pneumonia by drug-susceptible and MDR A. baumannii [ 8 ]. In the same line, preemptive LPC treatment in combination with ceftazidime has potentiated the in vivo antibacterial activity of ceftazidime in these severe infection models by MDR Pseudomonas aeruginosa [ 9 ]. Recently, Yadav et al reported that LPC in vitro potentiated the effect of a nonbactericidal concentration of polymexin B against the growth of Pseudomonas aeruginosa and Klebsiella pneumoniae [ 10 ].…”
Section: Introductionmentioning
confidence: 99%